An Investigation On How Special Needs Teachers In Bandung City Manage Their Emotions - Polla, Rina; Meilinda, Putri (Psychosocia : Journal of Applied Psychology and Social Psychology, 2024)
This study aims to describe the emotional regulation of Bandung City's Special School Category C teachers. The development of pupils with intellectual disabilities, who need patience, skills, and strong emotional regulation to navigate a variety of obstacles, is greatly aided by special needs teachers. Featuring 203 responders, this study used a quantitative method. The Emotion Regulation Questionnaire in Indonesian was used to gather data. According to the research results, 81.8% of participants had high emotional regulation, enabling them to modify their attitudes and actions in response to stressful circumstances. However, 18.2% of respondents showed low emotional regulation, which affects their ability to manage emotional stress. These findings underline the importance of developing supporting strategies to improve the psychological well-being of special needs teachers, which will ultimately improve the quality of education for students with special needs.